An introduced parasitic fly may lead to local extinction of Darwin's finch populations. Issue 2 (18th December 2015) - Koop, Jennifer A. H.; Kim, Peter S.; Knutie, Sarah A.; Adler, Fred; Clayton, Dale H.
Summary: Introduced pathogens and other parasites are often implicated in host population‐level declines and extinctions. However, such claims are rarely supported by rigorous real‐time data. Indeed, the threat of introduced parasites often goes unnoticed until after host populations have declined severely. The recent introduction of the parasitic nest fly, Philornis downsi, to the Galápagos Islands provides an opportunity to monitor the current impact of an invasive parasite on endemic land bird populations, including Darwin's finches. In this paper, we present a population viability model to explore the potential long‐term effect of P. downsi on Darwin's finch populations. The goal of our study was to determine whether P. downsi has the potential to drive host populations to extinction and whether management efforts are likely to be effective. Our model is based on data from five years of experimental field work documenting the effect of P. downsi on the reproductive success of medium ground finch Geospiza fortis populations on Santa Cruz Island. Under two of the three scenarios tested, the model predicted medium ground finches are at risk of extinction within the next century. However, sensitivity analyses reveal that even a modest reduction in the prevalence of the parasite could improve the stability of finch populations. We discuss the practicality of several management options aimed at achieving this goal. Synthesis and applications . Our study demonstrates the predicted high risk of local extinction of an abundant host species, the medium ground finch G. fortis due to an introduced parasite, P . downsi . However, our study further suggests that careful management practices aimed at reducing parasite prevalence have the potential to significantly lower the risk of host species extinction. Abstract : Our study demonstrates the predicted high risk of local extinction of an abundant host species, the medium ground finch G. fortis due to an introduced parasite, P . downsi . However, our study further suggests that careful management practices aimed at reducing parasite prevalence have the potential to significantly lower the risk of host species extinction.